Kebijakan Pimpinan dalam Peningkatan Sarana Prasarana dan Mutu Lulusan - utari, Della (Al-Miskawaih: Journal of Science Education, 2023)
This article aims to analyze the process and policy determination of Islamic boarding school leaders in improving the infrastructure and quality of graduates at the Al-Munawaroh Islamic Boarding School, Bangko District, Merangin Regency. The problem that is the focus of the discussion is how do Islamic boarding school leaders implement institutional policies to improve facilities and infrastructure to increase Islamic boarding school graduates? This article comes from qualitative research using data collection through observation, interviews, documentation and triangulation. Research findings show that leadership policies in improving Islamic boarding school facilities and infrastructure are carried out in stages; planning, procurement, maintenance and inventory. Achieving the quality of graduates is carried out by implementing 8 National Education Standards. Meanwhile, the realization of Islamic boarding school policies to achieve quality graduates is carried out by carrying out open communication, both formally and informally. Artikel ini bertujuan menganalisis proses dan penetapan kebijakan pimpinan pondok pesantren dalam meningkatkan sarana prasarana dan mutu lulusan di Pondok Pesantren Al-Munawaroh Kecamatan Bangko Kabupaten Merangin. Permasalahan yang menjadi fokus bahasan adalah bagaimana pimpinan pesantren melaksanakan kebijakan lembaga untuk meningkatkan sarana dan prasarana untuk meningkatkan lulusan pesantren? Artikel ini berasal dari penelitian kualitatif  dengan pengumpulan data secara observasi, wawancara, dokumentasi dan triangulasi. Temuan penelitian menunjukkan bahwa kebijakan pimpinan dalam peningkatan sarana dan prasarana pesantren dilakukan dengan tahapan; perencanaan, pengadaan, pemeliharaan, dan inventarisasi. Pencapaian mutu lulusan dilakukan dengan menerapkan 8 Standar Nasional Pendidikan. Sedangkan realisasi kebijakan peantren untuk mencapai mutu lulusan dijalankan dengan melakukan komunikasi terbuka, baik secara formal maupun informal.